1987
DOI: 10.1192/bjp.151.3.373
|View full text |Cite
|
Sign up to set email alerts
|

The General Health Questionnaire and the Detection of Emotional Disorder by General Practitioners

Abstract: This paper reports on a study of psychiatric morbidity in 920 patients attending 18 General Practitioners in Lewisham, South East London. Two indices of morbidity were computed on the basis of the patients responses to the General Health Questionnaire (GHQ) and the GPs' own estimates. Indices of the GPs' detection ability were found by comparing questionnaire and GP rating. The results are compared to those obtained by other workers in a sample of Manchester GPs. The GHQ gave a prevalence estimate of 42.9% whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
5

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 9 publications
8
39
5
Order By: Relevance
“…The General Health Questionnaire 28, which was used in this study, focuses on coping mechanisms and is therefore an important prognostic tool. Roughly one quarter of our patients (n=4) returned questionnaires that were positive for depression, which compared quite favorably with a rate of >40% obtained in a large sample of patients attending general practitioners [6]. This confirms the finding of a previous study that depression does not seem to be a major problem in osteosarcoma survivors [7].…”
Section: Discussionsupporting
confidence: 76%
“…The General Health Questionnaire 28, which was used in this study, focuses on coping mechanisms and is therefore an important prognostic tool. Roughly one quarter of our patients (n=4) returned questionnaires that were positive for depression, which compared quite favorably with a rate of >40% obtained in a large sample of patients attending general practitioners [6]. This confirms the finding of a previous study that depression does not seem to be a major problem in osteosarcoma survivors [7].…”
Section: Discussionsupporting
confidence: 76%
“…18 Previous studies using the GHQ in doctors have shown 22% to 46% have features of 21 In this study we have shown that wellbeing was best after a holiday and that it deteriorated after a normal working week -especially after a week of nights. A GHQ-12 score of >3 is the threshold for high levels of psychological symptoms.…”
Section: Effect On Psychological Well-beingsupporting
confidence: 50%
“…18 Previous studies using the GHQ in doctors have shown 22% to 46% have features of depression and anxiety, 19,20 compared to 18% of the general working population. 21 In this study we have shown that wellbeing was best after a holiday and that it deteriorated after a normal working week -especially after a week of nights.…”
Section: Effect On Psychological Well-beingmentioning
confidence: 99%
“…The earlier studies focussed mainly on ethnic group differences in GP consultation rates, certified sickness absence requests and the recognition rates of psychological distress in patients by GPs (e.g. Boardman, 1987;Johnson, Cross, & Cardew, 1983). However, although their general findings were consistent with significantly higher rates of GP consultations among persons of South Asian origin (especially Pakistani GP attenders), relative to those of Caribbean and Indian origin (see, e.g., Balarajan, Yuen, & Raleigh, 1989;Gillam, Jarman, White, & Law, 1989), there were several methodological problems with these studies.…”
Section: Service Utilization By Minority Ethnic Groupsmentioning
confidence: 99%